Predatory Behavior of the Basilica Spider, Mecynogea Lemniscata (Araneae, Araneidae) - Marianne B. Willey; Margaret A. Johnson; Peter H. Adler (Psyche: A Journal of Entomology, 1992)
Females of Mecynogea lemniscata (Walckenaer) are generalist predators. Sixteen behavioral acts were described for M. lemniscata preying on house flies, carpenter ants, and Asiatic oak weevils in the field and laboratory. Behavioral sequences varied with prey type, but generally began with plucking and diverged there-after. The predatory behavior of M. lemniscata is most similar to that of the higher araneids.